Environmental control in greenhouses for humid tropics - BOBBY T; Sinija V. R; Suresh A; Er. E. K. Kurien (Guide) (Tavanur 1997 Department of Irrigation and Drainage Engineering)
Environmental control in greenhouses for humid tropics
Environmental control in greenhouses for humid tropics